4.3k views
3 votes
What's the answer to this​

What's the answer to this​-example-1
User Hcheung
by
4.4k points

2 Answers

4 votes
General equation:
y = (slope)*x + (offset)
Replace y and x with the coordinates of any one of the two points
3 = (slope)*6 + (offset)
First find the slope:
(3-3)/(-4-6)=0/(-10)=0

Fill that in:
3 = 0*6 + (offset)
This simplifies to:
3 = (offset)
Now we have both the slope and the offset. Put them into the general equation
y = 0x + 3
of course, 0x is just 0. So we don't need to write that! It's enough to write:
y = 3

Notice that this is just a straight horizontal line, when graphed. The y coordinate is always the same regardless of what x is.

In the two points that the question gave, you can see this.

You can take a pattern from this:
Whenever there are two points, and their y values are the same but x values are different, then the equation is y = (the y-value of the points).
User Francisco QV
by
5.7k points
6 votes

Answer:

The full answer in the media.Good luck!

What's the answer to this​-example-1
User Adi Sutanto
by
5.2k points